Strategi Kepala Sekolah Meningkatkan Mutu Pembelajaran SMP Negeri 9 Prabumulih - Oktriani, Indah; Harapan, Edi; Wardiah, Dessy (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2021)
Abstract: The principal's strategy is an important factor in determining the success of quality improvement in schools. This study aims to identify and describe the role of the principal, the principal's strategy and the obstacles faced by the principal in improving the quality of learning. To achieve these objectives, this study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews and documentation study. Data analysis procedures are data reduction, data presentation and verification. Meanwhile, the research subjects were school principals, vice principals and teachers. The results showed that the role of the principal in improving the quality of learning was going well. The strategies that have been carried out by the principal in improving the quality of learning include: increasing the teaching ability of teachers, utilizing media and educational facilities, implementing regular supervision, establishing cooperation with the community and implementing strict time discipline for both teachers and students. The obstacle faced by the principal in improving the quality of learning at SMP Negeri 9 Prabumulih is the lack of permanent teaching staff, so that many teachers are used as honorary teachers and there are still teachers who teach not according to their educational qualifications in order to cover the shortage of teachers in certain subjects.